2019
DOI: 10.18499/2225-7357-2019-8-2-43-46
|View full text |Cite
|
Sign up to set email alerts
|

Features of Microsurgical Anatomy of the Small Intestine in Experimental Widespread Purulent Peritonitis

Abstract: Цель работы -изучение особенностей микроанатомического строения стенки тонкой кишки в условиях распространенного гнойного перитонита для обоснования применения микрохирургического кишечного шва.Материал и методы. Материалом исследования служили проксимальный, средний и дистальный отделы брыжеечной части тонкой кишки. У животных с экспериментальным перитонитом применен гистотопографический метод изготовления серийных поперечных и продольных гистотопограмм с окраской гематоксилином и эозином, и пикрофуксином по … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Inflammation of the abdominal cavity causes a decrease in the depth of intestinal crypts by 10%. According to the authors, the intestinal crypts are responsible for the renewal of the epithelial lining of the intestine for body balance control [25], it can be concluded that a decrease in the depth of the crypts is a morphological sign of a decrease in the regenerative activity of the epithelium of the small intestine [26]. The authors have shown that the absence of peristalsis leads to the loss of intestinal colonization resistance, translocation of pathogenic and opportunistic microflora to unusual habitats, bacteremia, the development of abdominal sepsis, and multiple organ failure [27,28].…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation of the abdominal cavity causes a decrease in the depth of intestinal crypts by 10%. According to the authors, the intestinal crypts are responsible for the renewal of the epithelial lining of the intestine for body balance control [25], it can be concluded that a decrease in the depth of the crypts is a morphological sign of a decrease in the regenerative activity of the epithelium of the small intestine [26]. The authors have shown that the absence of peristalsis leads to the loss of intestinal colonization resistance, translocation of pathogenic and opportunistic microflora to unusual habitats, bacteremia, the development of abdominal sepsis, and multiple organ failure [27,28].…”
Section: Resultsmentioning
confidence: 99%